Band Structure, Density of States, Structural Phase Transition and Metallization in CdO Under High Pressure - Pius, J. Jesse; Louis, C. Nirmala; Amalraj, A. (Orbital: The Electronic Journal of Chemistry, 2016)
The structural phase transition and metallization of the group II-VI compound semiconductor cadmium oxide (CdO) is investigated through its band structure obtained using the full potential linear muffin-tin orbital (FP-LMTO) method. The ground state properties and band gap values are compared with the experimental results. Under high pressure CdO undergoes a first order structural phase transition from the NaCl structure (B1) to the CsCl structure (B2). The band structure, density of states (DOS) and total energy are computed as a function of reduced volume for both NaCl and CsCl phases. The values of pressure under reduced volume are calculated using Birch-Murnaghan’s equation of state. The pressure corresponding to structural phase transition from NaCl structure (B1) to the CsCl structure (B2) is 0.9 Mbar in CdO. The metallization pressure PM is 1.2 Mbar. DOI: http://dx.doi.org/10.17807/orbital.v0i0.884